2021
DOI: 10.1186/s12885-021-08724-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-A is an Immunohistochemical biomarker for the efficacy of bevacizumab-containing chemotherapy for duodenal and jejunal adenocarcinoma

Abstract: Background The efficacy and safety of bevacizumab-containing chemotherapy for patients with metastatic duodenal and jejunal adenocarcinoma (mDJA) are unclear. The present study aimed to evaluate the efficacy of bevacizumab and to explore immunohistochemical markers that can predict the efficacy of bevacizumab for patients with mDJA. Methods This multicentre study included patients with histologically confirmed small bowel adenocarcinoma who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…After full-text revision, 57 studies were included, with a total of 35 176 patients. Among the 57 studies, 6 studies 27 , 28 , 29 , 30 , 31 , 32 were prospective cohort studies or phase 2 trials, and 51 studies 1 , 3 , 4 , 17 , 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 were retrospective in nature ( Table ; eTables 1 and 2 in…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full-text revision, 57 studies were included, with a total of 35 176 patients. Among the 57 studies, 6 studies 27 , 28 , 29 , 30 , 31 , 32 were prospective cohort studies or phase 2 trials, and 51 studies 1 , 3 , 4 , 17 , 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 were retrospective in nature ( Table ; eTables 1 and 2 in…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the palliative setting commonly studied all SIA localizations. Twenty-six studies 3 , 17 , 27 , 28 , 29 , 30 , 32 , 33 , 35 , 44 , 46 , 48 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 68 , 70 , 72 , 74 , 75 , 76 , 77 (65.0%) specified the chemotherapy regimens. Targeted agents were investigated in 7 studies, 31 , 60 , 61 , 63 , 64 , 71 , 76 of which most assessed bevacizumab.…”
Section: Resultsmentioning
confidence: 99%
“…The role of anti-angiogenic therapies, such as bevacizumab or ramucirumab, which were well established in metastatic CRC, underwent limited evaluation in advanced SBA, despite the known importance of the VEGF pathway in SBA [ 29 ]. Indeed, immunohistochemical expression of VEGF-A was recently reported as a potentially useful biomarker for the prediction of the efficacy of bevacizumab-based treatment in patients with advanced SBA [ 30 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Despite the lack of statistical comparison, the mPFS of XELOX plus bevacizumab is comparable to that of XELOX alone, as reported by the same institution (6). However, another retrospective multicenter study reported an mPFS of 15 months in 10 metastatic duodenal and jejunal adenocarcinoma patients treated with bevacizumab plus platinum (19). Notably, among patients treated with bevacizumab-based regimens, the mPFS of six patients with high vascular endothelial growth factor-A (VEGF-A) expression was significantly higher than four patients with low VEGF-A expression, implying that VEGF-A expression might act as a predictor for bevacizumab efficacy.…”
Section: Anti-vascular Therapymentioning
confidence: 55%